Conflitos socioambientais, educação ambiental e participação social na gestão ambiental - Saito, Carlos Hirro; Ruscheinsky, Aloisio; Bastos, Fábio da Purificação da; Nunes, Jacy Bandeira Almeida; Silva, Luciano Fernandes; Carvalho, Luiz Marcelo de [UNESP] (My University, 2011)
This is synthesis of the debates held during the round-table “Socioenvironmental conflicts, environmental education and social participation on environmental management”, at the V ENANPPAS (2010), which has focused on the discussion of four main themes: Socioenvironmental conflicts and the myths of social participation; Socioenvironmental conflicts and the uncertainty of conditions to environmental education immersed in problems and conflicts; Solution of Socioenvironmental conflitcts – actions mediated by instrumental rationality and emancipatory interest; Positive actions as dialogical-problematizing practice on concrete reality. From an initial provocative text, each member has brought his first contribution, followed by new questions as consequence of these speeches. The hole debate was recorded, transcripted and made a synthesis to present in this manuscript form.

Trata-se da síntese da mesa-redonda “Conflitos Socioambientais, Educação Ambiental e Participação Social na Gestão Ambiental” realizada no V ENANPPAS (2010), que teve como foco principal a discussão de quatro temas: Conflitos socioambientais e os mitos da participação social; Conflitos socioambientais e as incertezas das condições para a educação ambiental em meio aos problemas e conflitos; Resolução de Conflitos socioambientais – ações mediadas pela razão instrumental e interesse emancipatório; Ações positivas como práticas dialógicoproblematizadoras. A partir de um texto inicial provocativo, cada debatedor trouxe sua contribuição em forma de texto, seguida de novas questões oriundas dessas intervenções. O conjunto do debate foi gravado, transcrito e sintetizado para apresentação neste artigo.
Keywords: Environmental education; Socioenvironmental conflicts; Social participation; Instrumental rationality; Emancipatory interest; Paulo Freire; Educação ambiental; Conflitos socioambientais; Social; Razão instrumental; Interesse emancipatório; Paulo Freire